Can expelled cells/debris from a developing embryo be used for PGT? - Adva Aizer; Noa Harel-Inbar; Hagit Shani; Raoul Orvieto (BMC, 2021)
Abstract Background Preimplantation genetic testing (PGT) is offered to a wide range of structural and numerical chromosomal imbalances, with PGT- polymerase chain reaction (PCR), as the method of choice for amplifying the small DNA content achieved from the blastomere biopsy or trophectoderm (TE) biopsy, that might have a detrimental impact on embryonic implantation potential. Since human embryos cultured until Day-5-6 were noticed to expel cell debris/ fragments within the zona pellucida, we aimed to examine whether these cell debris/ fragments might be used for PGT, as an alternative to embryo biopsy. Methods Blastocysts, which their Day-3 blastomere biopsy revealed an affected embryo with single-gene defect, and following hatching leaved cell debris/fragments within the zona pellucida were analyzed. Each blastocyst and its corresponding cell debris/fragments were separated and underwent the same molecular analysis, based on multiplex PCR programs designed for haplotyping using informative microsatellites markers. The main outcome measure was the intra-embryo congruity of Day-3 blastomere biopsy and its corresponding blastocyst and cell debris/fragments. Results Fourteen affected embryos from 9 women were included. Only 8/14 (57.2%) of embryos demonstrated congruent molecular genetic results between Day-3 embryo and its corresponding blastocyst and cell debris/fragments. In additional 6/14 (42.8%) embryos, molecular results of the Day-3 embryos and their corresponding blastocysts were congruent, while the cell debris/fragments yielded no molecular diagnoses (incomplete diagnoses). Conclusions It might be therefore concluded, that in PGT cycles, examining the cell debris/fragments on Day-4, instead of Day-3 blastomere or Day-5 TE biopsies, is feasible and might avoid embryo biopsy with its consequent detrimental effect on embryos' implantation potential. Whenever the latter results in incomplete diagnosis, TE biopsy should be carried out on Day-5 for final genetic results. Further large well-designed studies are required to validate the aforementioned PGT platform.